THE ACQUISITION OF ENGLISH SYLLABLE TIMING BY NATIVE SPANISH SPEAKERS LEARNERS OF ENGLISH. AN EMPIRICAL STUDY’ - Gutierrez Diez, Francisco (International Journal of English Studies, 2001)
In this article we present part of the results of an empirical research on contrastive rhythm (English-Spanish). Of the several points dealt with in such a research (syllable compression, foot timing, syllable timing and isochrony of rhythmic units), we refer here to syllable duration in English and Spanish as well as the leaming of syllable duration by a group of advanced leamers of English whose first language is Spanish. Regarding the issue of syllable timing, a striking result is the equal duration of unstressed syllables in both languages, which challenges an opposite view underlying a teaching practice common among Spanish teachers of English to Spanish learners of that language. As for the interlanguage of the group of Spanish leamers of English, we comment on the presence of an interference error represented by a stressed/unstressed durational ratio mid way between the ratios for Spanish and English; we have also detected a developmental error related to the tempo employed by the leamers in their syllable timing, which is slower than the tempo produced by native speakers of English.